If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/8)*x^14-u = 3*u+6 // - 3*u+6
(3/8)*x^14-u-(3*u)-6 = 0
(3/8)*x^14-u-3*u-6 = 0
3/8*x^14 = -(-4*u-6) // : 3/8
x^14 = 8/3*(6-(-4*u))
x^14 = 8/3*(4*u+6) // ^ 1/14
abs(x) = (8/3)^(1/14)*(4*u+6)^(1/14)
x = (8/3)^(1/14)*(4*u+6)^(1/14) or x = -((8/3)^(1/14)*(4*u+6)^(1/14))
x in { (8/3)^(1/14)*(4*u+6)^(1/14), -((8/3)^(1/14)*(4*u+6)^(1/14)) }
| y/3+y/2-3 | | 6p+8=13p-6p-3 | | 9x+48=6x+50 | | 11+9=4x+30 | | -15=9r+1-6c | | x/2=13-x/3 | | -9+v/8=3 | | 5x^1/2+7=22 | | -4.7=8.4 | | 7x-19=5x+7 | | 9.2=5.7+h/6+4 | | 17+x-4=4x | | 28+19v=-8+15v | | 4=9/x | | 7y-(9-4y)=3(y-11) | | -5/3p+1/3+1=23/21 | | -n/4+1/6=5/4 | | 2/5x-18=-3 | | 9-9-1= | | 5(1+c)=4(c-3) | | x+12=3x-17 | | -3(m-2)=17 | | 0.333h-4(0.667-3)=0.667h-6 | | 35-4y=-9+7y | | -12/2+7 | | -1/9=x-5/6 | | 41-17=3(x-2) | | 3.75x+7.24=5.82x | | 7c-8-2c=1 | | 43m+(26/7)=(84/7) | | k+k+k=+18 | | y=-1E-05x+0.001 |